أبعاد التّجديد في مقاصد الشّريعة ومسوّغاته - موفق, نبيل (جامعة الوادي university of eloued, 2022)
تنطلق إشكالية هذا الموضوع من حصول أزمة وطروء خلل في واقع الأمّة ونهضتها، وأنّ منتهى حلّه ومعالجته يتوقّف عند ضرورة اللّجوء إلى البنية المنهجيّة لعلم مقاصد الشّريعة لتطوير النّظر الفقهي حتّى يستجيب لحلّ المشكلات النّازلة وتتطوّر أوضاع الأمّة على جميع الأصعدة، وعليه يجب علينا البحث في إمكانية تطوير النّظر المقاصدي بما يتواكب ومتطلّبات العصر ومستجدّاته ومعطياته، لاقتراح حلول ومخرجات لتلك الأزمة، ولمّا كان التّجديد المقاصدي بتلك الأهمّيّة كان لزاماً علينا أن نبحث في مفهومه وحقيقته، ومشروعيّته والدّواعي التّأسيسيّة التي يقوم عليها، وأهمّ مسوّغاته، وكذا البحث في قواعده، وهو ما تضمّنه هذا البحث بالمناقشة والبيان. Summary The problem of this issue stems from the occurrence of a crisis and an imbalance in the reality of the nation and its renaissance, and that the end of its solution and treatment depends upon the necessity of resorting to the systematic structure of the science of the purposes of the Sharia to develop jurisprudence in order to respond to the solution of the emerging problems and the development of the nation’s situation at all levels, and therefore we must research the possibility of developing The intentional consideration of what is in line with the requirements of the age, its developments and its data, to propose solutions and outputs for this crisis, and since the intentional renewal was of such importance, we had to examine its concept and truth, its legitimacy and the foundational reasons on which it is based, and its most important justifications, as well as researching its bases, which is what it is. By discussion and statement
مقال
Keywords: أبعاد ; التّجديد ; مقاصد ; الشّريعة ; المسوّغات